1965
DOI: 10.1139/p65-207
|View full text |Cite
|
Sign up to set email alerts
|

THE SPECTRUM OF SiH AND SiD

Abstract: Two new systems of SiH and SiD in the regions around 3 250 Å and 2 050 Å in addition to the well-known 2Δ−2Π system have been recorded in absorption and their rotational analysis (except for the 2Δ−2Π system of SiH) has been carried out. The new states are 2Σ+ at T0 = 30 974.69 cm−1 and 2Δ at T0 = 48 603.46 cm−1. The rotational constants for all the states known in SiD have been determined. The upper limit of the dissociation energy of SiH has been fixed at 24 680 cm−1 by predissociation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0

Year Published

1967
1967
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 1 publication
4
19
0
Order By: Relevance
“…Work on these two states includes the determination of ⌳-doubling transition frequencies for X 2 ⌸, 38,63,65,76 radiative lifetimes and oscillator strengths of the A 2 ⌬ϪX 2 ⌸ system, 43,45,47,61,64,74 various molecular constants, 55,56,67,72,78,79,84 transition moments, 66 ionization potentials, 55,80,81 and dissociation energies and enthalpies of formation. 55,59,64,68,80,81,83 To our knowledge, only a limited number of experimental papers deal with the higher excited states, but the extracted parameters useful to the present theoretical work are very few, limited mostly to term values. These papers include the work of Verma, 55 Herzberg et al, 60 Bollmark et al, 62 and Johnson and Hudgens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work on these two states includes the determination of ⌳-doubling transition frequencies for X 2 ⌸, 38,63,65,76 radiative lifetimes and oscillator strengths of the A 2 ⌬ϪX 2 ⌸ system, 43,45,47,61,64,74 various molecular constants, 55,56,67,72,78,79,84 transition moments, 66 ionization potentials, 55,80,81 and dissociation energies and enthalpies of formation. 55,59,64,68,80,81,83 To our knowledge, only a limited number of experimental papers deal with the higher excited states, but the extracted parameters useful to the present theoretical work are very few, limited mostly to term values. These papers include the work of Verma, 55 Herzberg et al, 60 Bollmark et al, 62 and Johnson and Hudgens.…”
Section: Introductionmentioning
confidence: 99%
“…55,59,64,68,80,81,83 To our knowledge, only a limited number of experimental papers deal with the higher excited states, but the extracted parameters useful to the present theoretical work are very few, limited mostly to term values. These papers include the work of Verma, 55 Herzberg et al, 60 Bollmark et al, 62 and Johnson and Hudgens. 82 The latter authors have located a state at 46 700Ϯ10 cm Ϫ1 and identified it as either a 2 ⌸ or a 2 ⌺ ϩ state.…”
Section: Introductionmentioning
confidence: 99%
“…The second system, B 2E+-X 2IIr at 3250 A first observed by Verma [5], exhibits a very complicated and irregular pattern and seems to be strongly predissociated above N=2 in Sill. Various extra lines could not be fitted into the B state model [5].…”
Section: Introductionmentioning
confidence: 86%
“…The second system, B 2E+-X 2IIr at 3250 A first observed by Verma [5], exhibits a very complicated and irregular pattern and seems to be strongly predissociated above N=2 in Sill. Various extra lines could not be fitted into the B state model [5]. Herzberg et al [7] 2 M. Lewerenz et al suggest a 2E+ or 21-I perturbing state with a minimum at large internuclear separation as the cause for the predissociation, whereas Bollmark et al [10], who report a rotational analysis of the B 2Y.+-X 21J r band, assume that there might be several perturbing states responsible for the irregular character in the spectrum.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation